Pengaruh Kesehatan Pada Masyarakat Pedesaan (Health Effects on Rural Communities) - Indah Azzahra Ritonga; Usiono Usiono (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Health is one of the main factors influencing the welfare of rural communities. This article examines in depth the relationship between health, economic productivity, and social development in rural communities. Apart from that, this journal also highlights the main challenges, such as lack of access to health services, low health education, and the negative impact of minimal infrastructure on community welfare. This study suggests the need for a holistic approach, involving government, communities and the private sector in improving health services.